Bury my heart at Wounded Knee - Simoneau, Yves.; Giat, Daniel; George, Clara; Quinn, Aidan; Beach, Adam, 1972-; Schellenberg, August; Simmons, J. K.; Schweig, Eric, 1967-; Studi, Wes.; Feore, Colm, 1958-; Tootoosis, Gordon; Thompson, Fred, 1942 August 19-; et al. ([United States] : HBO Home Entertainment ; Burbank, CA : distributed by Warner Home Video, 2011)
By 1876, most of the nation's American Indians had been forcibly relocated to reservation land. In the Dakota Territory, Red Cloud had settled his people on the great Sioux Reservation, becoming wards of the government. Other Sioux leaders saw this as defeat and continued to live in the traditional way, with legendary resistance. Then an economic depression struck, and gold was discovered in the Black Hills--on Sioux land. In this film, the lives of Charles Eastman-a Dartmouth-educated, Sioux doctor; Senator Henry Dawes-member of the Committee on Indian Affairs; and Sitting Bull intersect in a manner that seems fated. The question that faces the government and the Sioux seems to leave two answers: assimilation versus extermination? It is answered by the assassination of Sitting Bull and the massacre of hundreds of Indian men, women, and children by the 7th Cavalry at Wounded Knee Creek on Dec. 29, 1890.
Based on the book by Dee Alexander Brown.
Originally produced and broadcast in 2007.
Bonus features: Audio commentaries with director Yves Simoneau, Adam Beach and Aidan Quinn; "Making history," a behind-the-scenes look into the production of the film including interviews with cast and crew; "Heart of a people," historical perspective of the American Indian experience as depicted in the film; "Telling the story," journey of the book to the screen; Interactive on-screen historical guide prepared by the film's screenwriter; Photo gallery.
Director of photography, David Franco ; editors, Michael Ornstein, Michael Brown ; music by George S. Clinton.
Aidan Quinn, Adam Beach, August Schellenberg, J.K. Simmons, Eric Schweig, Wes Studi, Colm Feore, Gordon Tootoosis, Fred Thompson, Anna Paquin.
DVD format, region 1, widescreen (16:9 aspect ratio); Dolby digital.
Keywords: Sitting Bull, -- 1831-1890 -- Drama; Eastman, Charles A., -- 1858-1939 -- Drama; Dawes, Henry L. -- 1816-1903 -- Drama; Grant, Ulysses S. -- 1822-1885 -- Drama; Brown, Dee, -- 1908-2002 -- Television adaptations; United States. -- Army. -- Cavalry, 7th -- Drama; United States. -- Bureau of Indian Affairs -- Drama; Wounded Knee Massacre, S.D., 1890 -- Drama; Dakota Indians -- Wars, 1890-1891 -- Drama; Indians of North America -- Great Plains -- Drama; Indians, Treatment of -- North America -- Drama; Made-for-TV movies; Historical television programs; Films for the hearing impaired; Western plays; United States -- History -- 1865-1898 -- Drama